2014
DOI: 10.1371/journal.pone.0104556
|View full text |Cite
|
Sign up to set email alerts
|

Using Interactive Family Science Shows to Improve Public Knowledge on Antibiotic Resistance: Does It Work?

Abstract: The public plays an important role in controlling the emergence and spread of antibiotic resistance. A large British survey showed that there is still public misunderstanding about microbes and antibiotics. e-Bug, a European DG Sanco sponsored project, aims to disseminate a school antibiotic and hygiene educational pack and website across Europe. Interactive science shows based on the e-Bug educational packs were developed to take the key health and hygiene messages from the e-Bug school resources to families.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…Previous research has shown improvements in student knowledge about other infection related topics after the delivery of an e-Bug lesson, activity and e-Bug online games (Lecky et al 2010;Hawking et al 2013;Lecky et al 2014;Hale et al 2017;Eley et al 2018;Eley et al 2019) and this study contributes to this growing literature.…”
Section: Comparison With Existing Literaturementioning
confidence: 73%
“…Previous research has shown improvements in student knowledge about other infection related topics after the delivery of an e-Bug lesson, activity and e-Bug online games (Lecky et al 2010;Hawking et al 2013;Lecky et al 2014;Hale et al 2017;Eley et al 2018;Eley et al 2019) and this study contributes to this growing literature.…”
Section: Comparison With Existing Literaturementioning
confidence: 73%
“…The benefits of using e-Bug to deliver health education around microbes, hygiene and antibiotics have been well documented (Hawking et al 2013;Lecky et al 2010Lecky et al , 2014McNulty et al 2011) with improvements in knowledge increasing after the delivery of an e-Bug lesson (Hawking et al 2013;Lecky et al 2010Lecky et al , 2014. Our research adds to the body of literature to support the value of the e-Bug resources as 94% of respondents rated the overall e-Bug resource as excellent or good.…”
Section: Comparison With Existing Literaturementioning
confidence: 72%
“…Peer-based programmes are effective because (i) they use role models to influence the majority through modelling behaviour or education, (ii) young people are most influenced by their peer group and people they find credible or with whom they identify with (peers in their own school), and (iii) social networks exist organically within peer groups, thus providing a natural communication channel for influencing change [11]. The e-Bug PE resources have been used to teach young people aged 9 to 14 years in schools or science shows [12]. The PE resources have also been used by young people to educate their younger peers, which has resulted in significant increases in student knowledge and confidence in both groups [10].…”
Section: Introductionmentioning
confidence: 99%